Organisational Baseline Study: Overview report for My Loi CSV, Vietnam (VN02) - Duong, Minh Tuan; Hai, Le Van; Simelton, Elisabeth (2014)
This report covers the Organisational Baseline Study (OBS) for the CCAFS climate-smart village My Loi in central Viet Nam. During October and November 2014 interviews were conducted with ten organisations working or collaborating with farmers and/or the community in Ky Anh district in Ha Tinh province. The My Loi research site lies in the uplands of the north central coast. The region has four but increasingly variable seasons, increase in frequency and magnitude of storms and tropical low-pressure systems, increase in intensity of dry and hot westerly wind (Laos wind). The main farming systems comprise a blend of crop-livestock systems with the main crops being rainfed rice, cassava, peanut, and acacia. This OBS report supplements the qualitative village baseline studies at the same location. The objectives of the organisational baseline study are to:  Provide indicators to monitor changes in behaviours and practices of locally relevant organisations that have climate change related activities in Ha Tinh over time  Understand the provision of information/services at the local level that informs farmers’ decision making about their livelihood strategies in response to climate change